RESPON KANDUNGAN ISOFLAVON DAIDZEINPADA LEGUM Alysicarpus vaginalis TERHADAP VARIASI DOSIS PUPUK FOSFOR (Response of Daidzein Isoflavone Content in Alysicarpus vaginalis Legume to Variations in Phosphorus Fertilizer Doses) - Suharto, Prihutomo; Gusri, Rahmat; Kertiyasa, I Kadek Yoga; Didik Widiarta, I Putu Gede (Universitas Nusa Cendana, 2025)
This study is grounded in the significance of daidzein as a phytoestrogen with potential to enhance livestock reproductive performance, while its availability in conventional feed ingredients remains limited. Alysicarpus vaginalis is a local legume species exhibiting relatively high phenolic and flavonoid compounds, including isoflavones, making this information crucial for developing phytogenic based functional feed. This research aimed to evaluate the effect of varying phosphorus fertilizer doses on daidzein isoflavone content in Alysicarpus vaginalis. An experimental study was conducted using a Completely Randomized Design (CRD) with five phosphorus dose treatments (0, 10, 20, 30, and 40 kg P/ha) and three replications. The methodology included: (1) isoflavone extraction via 70% ethanol maceration, (2) extract concentration using a rotary evaporator, and (3) quantitative analysis of daidzein content in phosphorus fertilized Alysicarpus vaginalis using High-Performance Liquid Chromatography (HPLC). Increasing phosphorus doses (0–40 kg P/ha) significantly (P<0.05) elevated daidzein content from 0.0922 g/100 g sample (control, 0 kg P/ha) to 2.9978 g/100 g sample at the highest dose (40 kg P/ha). Statistical analysis revealed a strong positive correlation between phosphorus dosage and daidzein accumulation (R² = 0.985). Phosphorus fertilizer application enhances daidzein production in Alysicarpus vaginalis, implying potential for functional feed development to support livestock health and productivity.